The Russian Federation in Transition : External Developments - Christensen, Benedicte (IMF Working Papers; Working Paper, 1993)
This paper discusses Russia's balance of payments developments in recent years: the initial macroeconomic imbalances and systemic shocks which set the stage for the critical balance of payments difficulties Russia faced in the early 1990s; the lessons from the early phases of Russia's economic reforms; the choices faced by the Russian Government and the international community in supporting the government's reform efforts; and the external debt situation. This analysis also points to external adjustment issues which Russia will face in the period ahead, including the potential for an early reversal of the export decline and the nature of external financing and debt problems.